In the shadow of Bezalel : Aramaic, biblical, and ancient Near Eastern studies in honor of Bezalel Porten - Botta, Alejandro F., 1960- (Culture and History of the Ancient Near East, 2013)
Twenty nine scholars from Israel, Europe and the Americas came together to honor and celebrate Prof. Bezalel Porten's (Emeritus, Dept. of History of the Jewish People, Hebrew University of Jerusalem) academic career. Covering a wide variety of topics within Aramaic, Biblical, and ancient Near Eastern Studies, In the Shadow of Bezalel offers new insights and proposals in the areas of Aramaic language, paleography, onomastica and lexicography; ancient Near Eastern legal traditions, Hebrew Bible, and social history of the Persian period.